Construction manager’s technical competencies in Malaysian construction projects - Abdullah, Abd Halid; Yaman, Siti Khalijah; Mohammad, Hairuddin; Hassan, Padzil Fadzil (Emerald Publishing Limited, 2018)
Problems of Malaysian construction industry have often been associated, in part to incompetent construction manager (CM) when managing the construction projects. Although various education and training provisions have been introduced, critics argue that the provisions have not been effective. Central in the debate on the adequacy of the CM education and training offered is the answer to the question of “what constitutes the technical competency of the CM?” The purpose of this paper is to present the study that identifies the technical competencies required by the CM to address the question. Design/methodology/approach – Multi-layered thematic analysis of literature was first carried out to identify the technical competency elements. Then, interviews were undertaken to confirm the elements of competencies. It was followed with questionnaire surveys to test the validity of the technical competencies against different contractors’ category and grade/size. Findings – The findings suggest that the technical competencies of CM are generic, regardless of the size of construction organisation or the types of projects they undertake. A total of 16 CM technical competencies were identified which include the ability to manage: staff, materials, labour, plant, sub-contractors, safety, money, quality, time, environment, site administration, pre-construction activities, project closeout and handover, third parties, computer literacy, and construction contract. Originality/value – The findings suggest that generic education and training is possible to develop technically competent CM. It also provides insights to the CM technical competencies which the industry is expecting.